The relationships between Dark Tetrad traits and adolescent cyberbullying and cybertrolling with online time and life satisfaction as moderators - Masoumeh Alavi; Anchal Garg; Niroshya Wanigatunga (Discover Psychology)
Abstract Cyberbullying and cybertrolling on social media have significant implications for mental health. The Dark Tetrad traits are associated with antisocial online behaviours. However, the influence of time spent social media and life satisfaction on these relationships is not fully understood. This study investigated the relationships of Dark Tetrad traits (Machiavellianism, narcissism, psychopathy, and sadism) with cyberbullying and cybertrolling in 189 Australian adolescents (aged 16–19; M = 17.29, SD = 0.89). Using purposive sampling, data were collected via an online survey with self-report questionnaires, including the Short Dark Tetrad Scale, Cyber-Aggression Scale, Global Assessment of Internet Trolling, and Brief Multidimensional Student’s Life Satisfaction Scale. Multiple regression analyses indicated that psychopathy and sadism were significant predictors of antisocial online behaviours, while Machiavellianism and narcissism were not significant predictors. Time spent online and life satisfaction did not moderate the relationships between Dark Tetrad traits and these behaviours. These findings can inform early assessments and educational interventions while highlighting the importance of parental awareness of personality traits and online risks. Implementing these recommendations can help reduce maladaptive online behaviours among adolescents, fostering a safe online environment and mitigating the impacts of cyberbullying and cybertrolling.